Effects of polymer molecular weight on relative oral bioavailability of curcumin - Lin LC (Dove Medical Press, 2012)
Yin-Meng Tsai,1 Wan-Ling Chang-Liao,1 Chao-Feng Chien,1 Lie-Chwen Lin,1,2 Tung-Hu Tsai,1,31Institute of Traditional Medicine, School of Medicine, National Yang-Ming University, 2National Research Institute of Chinese Medicine, 3Department of Education and Research, Taipei City Hospital, Taipei, TaiwanBackground: Polylactic-co-glycolic acid (PLGA) nanoparticles have been used to increase the relative oral bioavailability of hydrophobic compounds and polyphenols in recent years, but the effects of the molecular weight of PLGA on bioavailability are still unknown. This study investigated the influence of polymer molecular weight on the relative oral bioavailability of curcumin, and explored the possible mechanism accounting for the outcome.Methods: Curcumin encapsulated in low (5000–15,000) and high (40,000–75,000) molecular weight PLGA (LMw-NPC and HMw-NPC, respectively) were prepared using an emulsification-solvent evaporation method. Curcumin alone and in the nanoformulations was administered orally to freely mobile rats, and blood samples were collected to evaluate the bioavailability of curcumin, LMw-NPC, and HMw-NPC. An ex vivo experimental gut absorption model was used to investigate the effects of different molecular weights of PLGA formulation on absorption of curcumin. High-performance liquid chromatography with diode array detection was used for quantification of curcumin in biosamples.Results: There were no significant differences in particle properties between LMw-NPC and HMw-NPC, but the relative bioavailability of HMw-NPC was 1.67-fold and 40-fold higher than that of LMw-NPC and conventional curcumin, respectively. In addition, the mean peak concentration (Cmax) of conventional curcumin, LMw-NPC, and HMw-NPC was 0.028, 0.042, and 0.057 µg/mL, respectively. The gut absorption study further revealed that the HMw-PLGA formulation markedly increased the absorption rate of curcumin in the duodenum and resulted in excellent bioavailability compared with conventional curcumin and LMw-NPC.Conclusion: Our findings demonstrate that different molecular weights of PLGA have varying bioavailability, contributing to changes in the absorption rate at the duodenum. The results of this study provide the rationale for design of a nanomedicine delivery system to enhance the bioavailability of water-insoluble pharmaceutical compounds and functional foods.Keywords: absorption, duodenum, molecular weight, poly(lactic-co-glycolic acid), PLGA, relative oral bioavailability